Development of Discovery Learning-Based Audio Visual Media to Improve Thematic Learning Outcomes - Dwi Anjarwani; Herpratiwi Herpratiwi; Ryzal Perdana (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2023)
The problem in this study is that learning still uses the lecture method, there are still elementary schools that have not used audio-visual media, there are still educators who cannot operate audio-visual media, there are still students who have grades below the KKM. The aims of this study were (1) to analyze the characteristics of discovery learning-based audio-visual media to improve thematic learning outcomes of Class III Cluster IV Gadingrejo students and (2) to analyze the effectiveness of discovery learning-based audio-visual media to improve thematic learning outcomes of Class III Cluster IV students Gadingrejo. The type of this research is Borg & Gall Modification Budiyono's development research (R&D). The population in this study was all Class III Cluster IV Gadingrejo students with a total of 176 students. The subjects of this study amounted to 21 students. The results of the study can be seen from the differences in thematic learning outcomes in the experimental class. The average pretest score for the experimental class was 54.28 and the posttest average score for the experimental class was 79.04. Likewise, it can be seen from the average value of N-Gain or increased knowledge of the experimental class is 0.4642 which is in the "Moderate" category, meaning that the development of audio-visual media based on discovery learning is effective for improving the thematic learning outcomes of Class III Students of Cluster IV Gadingrejo. The tcount results obtained a value of 3.7415 while t table (5%; n-1) is 2.0860, these results can be interpreted that the results of students' posttests are better than the pretest results of students who study using audio-visual media based on discovery learning.